Between Past and Future: The Mission of University of L’Aquila and Its Action on Energy and Climate Change - Curci, Gabriele; de Monte, Filippo; Nardecchia, Annamaria; Tozzi, Anna (Journal of Sustainability Perspectives, 2021)
For the University of L’Aquila, sustainability and civic engagement are key commitments. Actions to enhance and safeguard the territory and to improve the community wellbeing are even more meaningful in a city that, after the earthquake of 2009, is re-thinking its social and economic backbone. The aim to provide buildings with a high level of seismic security, of energy efficiency and resources saving, has been particularly challenging, but that also offered an opportunity. The participation to the UI Green Metric WUR has been a natural consequence of this process of renovation. Moreover, throughout the data collection and analysis, UI GM rankings stimulates the cross disciplinary cooperation in research, innovation, social and civic engagement.Concerning “Energy and Climate Change” the University could take the opportunity to exploit the competencies of research teams worldwide known working in renewable energies production (solar, wind, hydropower), building efficiency and retrofitting, environmental impacts. The University is member of the Italian University Network for Sustainable Development, which offered guidelines to implement energy and climate change related politics. The improvements of building focused on: smart illumination appliances (61% of the area), smart automation of heating/cooling (90% of the area), renewable energy production (PV and solar thermal), and integration of climate action into the strategic plan.